The Relationship between Population Dynamic and Garang River Upstream Environment in Central Java, Indonesia - Puji Hardati; Dewi Liesnoor Setyowati; Thriwaty Arsal; Muhammad Amin; Edy Trihatmoko (Indonesian Journal of Geography, 2022)
The interaction of the human population with nature can cause environmental damage such as the degradation of the watershed carrying capacity. Therefore, this study aimed to analyze the relationship between population dynamic and the upstream environment alongside Garang River using four villages including Munding, Lerep, Kalirejo, and Pakintelan. Data were collected from several stakeholders including selected heads of households supported by key informants such as community leaders and the river care communities using field observation, a household survey through questionnaires, in-depth interviews, and documentation. The households used as samples were selected through proportional random sampling and the data retrieved were analyzed through a descriptive quantitative method which involved the cross-tabulation of household data on economic activities and environmental management practices. It was discovered that 1) the population of the Garang River’s upstream was very dynamic with growth rates varying from 1.05% to 3.93%, 2) the main livelihood of the population and dominant land use was the agricultural sector, 3) the community realized that the harmonic relationship with the environment was a critical condition to support farming activities and fulfil daily necessities, and 4) the society kept maintaining the river through different activities such as "bersih sungai" or river cleaning and "sedekah bumi" or thank-giving to the environment. Moreover, the harmonic relationship between the people and the river environment is in form of several activities. These included waste management, cleaning rivers, maintaining clean waterways, actions to create a clean and healthy environment, and joining the efforts to care for the environment. The harmony was observed to have been realized through the integration of diversity, interdependence, unity, and the value of providing care.